Pulmonary Thromboembolectomy for Acute Pulmonary Thromboembolism - Yi, Inho (Korean Society for Thoracic and Cardiovascular Surgery, 2011)
BACKGROUND: Acute pulmonary thromboembolism is fatal because of abruptly occurring hypoxemia and right ventricular failure. There are several treatment modalities, including anticoagulation, thrombolytics, ECMO (extracorporeal membrane oxygenator), and thromboembolectomy, for managing acute pulmonary thromboembolism. MATERIALS AND METHODS: Medical records from January 1999 to December 2004 at our institution were retrospectively reviewed for pulmonary thromboembolectomy. There were 7 patients (4 men and 3 women), who underwent a total of 8 operations because one patient had post-operative recurrent emboli and underwent reoperation. Surgery was indicatedfor mild hypoxemia and performed with CPB (cardiopulmonary bypass) in a beating heart state. RESULTS: The patients had several symptoms, such as dyspnea, chest discomfort, and palpitation. Four patients had deep vein thromboembolisms and 3 had psychotic problems, specifically schizophrenia. Post-operative complications included hemothorax, pleural effusion, and pericardial effusion. There were two hospital deaths, one each by brain death and right heart failure. CONCLUSION: Emergency operation should be performed when medical treatments are no longer effective.